The Impact of Pancreatic Enzyme Supplementation on Postprandial Responses of Glucagon-Like Peptide-2 in Patients with Chronic Pancreatitis and Pancreatic Exocrine Insufficiency - Knop, Filip K; Vilsbøll, Tina; Lund, Asger; Krarup, Thure; Holst, Jens J; Hornum, Mads (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Plasma concentrations of glucagon-like peptide-2.